A Bibliometric Review of Creative Economy Entrepreneurship: Implications for Community Empowerment Strategies - Judijanto, Loso; Puspa, Leonora; Thalib, Najdah (West Science Interdisciplinary Studies, 2024)
This study presents a bibliometric review of creative economy entrepreneurship, focusing on its implications for community empowerment strategies. Using data from Google Scholar and Scopus, the analysis covers publications from 1997 to 2024. The VOSviewer software was used to conduct co-citation, keyword co-occurrence, and network mapping analyses to identify key research trends, influential authors, and emerging topics. Results show that "creative industry" is central to discussions, with frequent connections to themes like "local wisdom," "business development," and "digital transformation." The study highlights the growing importance of digital tools and sustainability in creative entrepreneurship, particularly in empowering marginalized communities. The analysis also reveals distinct author collaboration clusters, pointing to limited interdisciplinary interactions that could benefit from further exploration. Overall, the findings suggest that while creative economy entrepreneurship is a promising tool for community empowerment, more research is needed on digital inclusion, sustainability, and cross-disciplinary collaboration. This review contributes to the understanding of how creative industries can drive both economic growth and social empowerment.